2017
DOI: 10.1371/journal.pone.0172991
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cerebral tissue oxygen saturation during neonatal extracorporeal membrane oxygenation

Abstract: ObjectivesExtracorporeal membrane oxygenation support is indicated in severe and refractory respiratory or circulatory failures. Neurological complications are typically represented by acute ischemic or hemorrhagic lesions, which induce higher morbidity and mortality. The primary goal of this study was to assess the prognostic value of cerebral tissue oxygen saturation (StcO2) on mortality in neonates and young infants treated with ECMO. A secondary objective was to evaluate the association between StcO2 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…NIRS uses near-infrared light to measure trends in cerebral oxygenation ( 86 ). In neonatal ECMO patients, case series have reported decreased brain tissue oxygenation in patients that later demonstrated cerebral injury on neuroimaging ( 87 ). Only one study has studied cerebral NIRS in adults, finding that cerebral oxygenation significantly responded to hemodynamic intervention and that non-responders were more likely to have ischemic cerebral complications ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…NIRS uses near-infrared light to measure trends in cerebral oxygenation ( 86 ). In neonatal ECMO patients, case series have reported decreased brain tissue oxygenation in patients that later demonstrated cerebral injury on neuroimaging ( 87 ). Only one study has studied cerebral NIRS in adults, finding that cerebral oxygenation significantly responded to hemodynamic intervention and that non-responders were more likely to have ischemic cerebral complications ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…In paediatric patients, there is further evidence. Clair et al published a prospective study in 2017 assessing the prognostic value of cerebral NIRS in 34 infants under 3 months of age on ECMO 27. The mortality in this study was 50% and evaluation of the NIRS data revealed than non-survivors had significantly lower NIRS than survivors.…”
Section: Clinical Applicationsmentioning
confidence: 50%
“…Second, only patients receiving V-A ECMO were included in our study; thus, conclusions obtained from the current study may not be extrapolated to those with V-V ECMO. However, Clair et al ( 19 ) reported the mean CrSO 2 for the whole time of ECMO support, the duration of CrSO 2 below the threshold of 20% from baseline, and the duration of CrSO 2 <50% were not different in patients with V-V ECMO compared to V-A ECMO. Third, we only compared CrSO 2 values between survivors and non-survivors, as the small sample size is a limitation in adjusting for suspected confounding factors.…”
Section: Discussionmentioning
confidence: 95%